A course on mathematical logic - Srivastava, S. M. (Springer, 2017)
Preface -- Syntax of first order logic -- Semantics of first-order languages -- Propositional logic -- Proof and metatheorems in first-order logic -- Completeness theorem and model theory -- Recursive functions and arithmetization of theories -- Incompleteness theorems and recursion theory -- References -- Index